Heterogeneous magnetism and kinetic arrest in antiperovskite Mn3-xNixGaC compounds with Ni2MnGa Heusler insertions - Cakir, O.; Dias, E.; Priolkar, K. R.; Hoser, A.; Farle, M.; Acet, M. (AMER PHYSICAL SOC, 2020)
Mn-based antiperovskite compounds in the form Mn(3)AX, where A is a main group element and X is C or N, undergo magnetostructural transitions with which these materials acquire magnetocaloric, giant magnetoresistance, and spin-transport properties, which can be modified or tailored by manipulating the compositions of numerous compounds. This enables closer investigations and better understandings of the underlying principles governing these properties. Mn3-xNixGaC, which is a derivative of the prototype Mn3GaC antiperovskite, would normally be expected to form a cubic structure with a homogeneous composition. Contrary to this, we find that the addition of Ni leads to a heterogenous compound consisting of an antiperovskite part and a Ni2MnGa Heusler insertions. The system shows kinetic arrest features, which we study as a function of Ni composition using the techniques of x-ray diffraction, magnetization, and neutron diffraction under a magnetic field.
Keywords: THERMODYNAMIC PROPERTIES; ELECTRONIC-PROPERTIES; STABILITY; 1ST; Materials Science; Physics